A multilevel investigation on antecedents for employees' exploration of enterprise systems. Issue 4 (4th July 2019) - Peng, Zeyu; Guo, Xitong
ABSTRACT: Employees' system exploration behaviour is critical for contemporary firms to fully derive benefits from investments in an enterprise system (ES). Based on the adaptive structuration theory (AST), it is proposed that employees' exploration of an ES is mainly influenced by three fundamental components at different theoretical levels: task, technology, and the organisational environment. Accordingly, we develop a multilevel research model to interpret how task variety, system modularity, and local management commitment jointly affect employees' system exploration. Our model is tested with a survey of ES users in 35 business units of six firms that have already implemented enterprise resource planning (ERP) systems, and several meaningful findings were discovered. At the individual level, both system modularity and task variety can directly affect employees' system exploration, and the direct effect of system modularity is positively moderated by task variety. Further, unit-level local management commitment can either directly affect, or positively moderate, the relationship between task variety and system exploration. Limitations and implications for research and practice are discussed.